Soil Contamination of leachates from wood preservative and agropesticides affecting seed germination - Carlson Tawi, Anak Daud (Universiti Malaysia Sarawak, UNIMAS, 2013)
The purpose of this study was to compare the effects of the concentrations of CCA preservatives and agropesticides such as Chlorpyrifos, Cypermethrin and Permethrin. Two seed species, okra (Abelmoschusexculentus) and tomato (Solanumlycopersicum) were used for this experiment. The seed species were germinated with different concentrations of CCA preservative, Chlorpyrifos, Cypermethrin and Permethrin which are being treated in filter paper and soil. 4 replicated were done for all the treatments. The seed germinations testing were evaluated for seven consecutive days. The total of the seed germinated were recorded and the mean were obtained. It was found that there is interaction between the chemicals however it was not scientifically practical to compare the chemicals because the concentrations for each chemical are different. Thus, individual chemical was compared at their concentration levels. In most cases, we can see that the numbers of germinating seeds are decreasing as we increase the concentration. It is also found that as the concentration of chemical increases, the pH value also decreases. In another word, the higher the concentrations of the chemicals, the more acidic it is. This phenomenon can explain why the seeds are acting negatively on its germination due to the unfavourable acidity. If we were to compare the effectiveness of agrochemicals on the prohibition of seed germination, CCA is found to be highly phytotoxic to the seeds. No germination is detected when 6% of CCA solution is used. Chlorpyrifos of higher concentrations also prohibited the seed germinations.